Interactions and effects of a stannous-containing sodium fluoride dentifrice on oral pathogens and the oral microbiome - Chen, Danyan; Chew, Dillon; Xiang, Qianfeng; Lam, TzeHau; Dai, Yajie; Liu, Jiquan; Wang, Lijiang; He, Tao; Strand, Ross; Zhang, Xiaolan; Lim, Linda; Xu, Jian; et al. (Frontiers in Microbiology, 2024)
Numerous studies have investigated the effects of stannous ions on specific microbes and their efficacy in reducing dental plaque. Nonetheless, our understanding of their impact on the oral microbiome is still a subject of ongoing exploration. Therefore, this study sought to evaluate the effects of a stannous-containing sodium fluoride dentifrice in comparison to a zinc-containing sodium fluoride dentifrice and a control group on intact, healthy oral biofilms. Utilizing the novel 2bRAD-M approach for species-resolved metagenomics, and FISH/CLSM with probes targeting periodontal and caries associated species alongside Sn 2+ and Zn 2+ ions, we collected and analyzed in situ biofilms from fifteen generally healthy individuals with measurable dental plaque and treated the biofilms with dentifrices to elucidate variations in microbial distribution. Although significant shifts in the microbiome upon treatment were not observed, the use of a stannous-containing sodium fluoride dentifrice primarily led to an increase in health-associated commensal species and decrease in pathogenic species. Notably, FISH/CLSM analysis highlighted a marked reduction in representative species associated with periodontitis and caries following treatment with the use of a stannous-containing sodium fluoride dentifrice, as opposed to a zinc-containing sodium fluoride dentifrice and the control group. Additionally, Sn 2+ specific intracellular imaging reflected the colocalization of Sn 2+ ions with P. gingivalis but not with other species. In contrast, Zn 2+ ions exhibited non-specific binding, thus suggesting that Sn 2+ could exhibit selective binding towards pathogenic species. Altogether, our results demonstrate that stannous ions could help to maintain a healthy oral microbiome by preferentially targeting certain pathogenic bacteria to reverse dysbiosis and underscores the importance of the continual usage of such products as a preventive measure for oral diseases and the maintenance of health.